2014
DOI: 10.3389/fnagi.2014.00054
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the use of Serious Games in people with Alzheimer's Disease, related disorders and frailty

Abstract: Alzheimer's disease and other related disorders (ADRD) represent a major challenge for health care systems within the aging population. It is therefore important to develop better instruments to assess the disease severity and progression, as well as to improve its treatment, stimulation, and rehabilitation. This is the underlying idea for the development of Serious Games (SG). These are digital applications specially adapted for purposes other than entertaining; such as rehabilitation, training and education.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
138
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(161 citation statements)
references
References 59 publications
6
138
0
8
Order By: Relevance
“…Regular exercise at home could help to prevent diseases aggravated by a sedentary life imposed by conditions such as cardiovascular diseases and stroke [14]. Furthermore, health benefits from exercises could contribute to the reduction of health care costs for insurance companies and the public health system as well [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Regular exercise at home could help to prevent diseases aggravated by a sedentary life imposed by conditions such as cardiovascular diseases and stroke [14]. Furthermore, health benefits from exercises could contribute to the reduction of health care costs for insurance companies and the public health system as well [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Serious games, another method of ICT defined as digital applications specialized for purposes other than diversion (e.g., training and educating, communicating, rehabilitation) [90], have not been used for neuropsychological assessments. The applications of serious games have been restricted to rehabilitation for enhancing cognitive and physical function in different disorders with EDF, such as Alzheimer's disease, mild cognitive impairment [91][92][93][94][95][96][97][98][99] and treatment of mental health disorders [100].…”
Section: Neuropsychological Assessment In Simulated Environmentsmentioning
confidence: 99%
“…Focussing on the application of digital games for persons living with dementia, a review revealed that the majority of games used are, again, commercial games [172]. Despite this, serious games -as opposed to off-theshelf games -have been identified as a potential clinical tool for dementia [173].…”
Section: Healthcarementioning
confidence: 99%